Zabrnięcie w rewolucję: marksizm analityczny, racjonalność i działanie zbiorowe - Bertram, Christopher; Carling, Alan (Człowiek i Społeczeństwo, 2016)
Right-wing critics have long used the theory of rational choice to pour scorn on the Marxist theory of revolution, because, they say, free-rider considerations will deter any rational self-interested worker from engaging in revolutionary action. This contention poses an especial problem for Analytical Marxists, who also utilise rational choice models to understand the micro-foundations of collective action. It turns out, however, that if the worker’s decision to join a collective action is conceived more realistically, not as a once-for-all commitment, but as a recurrent process affected continuously by the actions of others, then a much richer repertoire of outcomes begins to appear within the theory – matching those found in history itself. This paper develops simple models of collective action that display this broader range of possibilities. These include convergence to a stable level of collective engagement, oscillation over time between different levels of engagement, and truly chaotic behaviour, in which levels of engagement are never repeated.